Barrett's Registry Collaboration of academic centers in Ireland reveals high progression rate of low-grade dysplasia and low risk from nondysplastic Barrett's esophagus: report of the RIBBON network. Issue 10 (19th March 2020) - O'Byrne, Lisa M; Witherspoon, Jolene; Verhage, Roy J J; O'Brien, Marie; Muldoon, Cian; Ryan, Ciara; Buckley, Martin; Murphy, Thomas; Reynolds, Rob; Patchett, Stephen; Kay, Elaine; Azam, Halsema; et al.
Summary: Barrett's esophagus (BE) is the main pathological precursor of esophageal adenocarcinoma (EAC). Progression to high-grade dysplasia (HGD) or EAC from nondysplastic BE (NDBE), low-grade dysplasia (LGD) and indefinite for dysplasia (IND) varies widely between population-based studies and specialized centers for many reasons, principally the rigor of the biopsy protocol and the accuracy of pathologic definition. In the Republic of Ireland, a multicenter prospective registry and bioresource (RIBBON) was established in 2011 involving six academic medical centers, and this paper represents the first report from this network. A detailed clinical, endoscopic and pathologic database registered 3, 557 patients. BE was defined strictly by both endoscopic evidence of Barrett's epithelium and the presence of specialized intestinal metaplasia (SIM). A prospective web-based database was used to gather information with initial and follow-up data abstracted by a data manager at each site. A total of 2, 244 patients, 1, 925 with no dysplasia, were included with complete follow-up. The median age at diagnosis was 60.5 with a 2.1:1 male to female ratio and a median follow-up time of 2.7 years (IQR 1.19–4.04), and 6609.25 person years. In this time period, 125 (5.57%) progressed to HGD/EAC, with 74 (3.3%) after 1 year of follow-up and 38 (1.69%) developed EAC, with 20 (0.89%) beyond 1 year. The overall incidence of HGD/EAC was 1.89% per year; 1.16% if the first year is excluded. The risk of progression to EAC alone overall was 0.57% per year, 0.31% excluding the first year, and 0.21% in the 1, 925 patients who had SIM alone at diagnosis. Low-grade dysplasia (LGD) progressed to HGD/EAC in 31% of patients, a progression rate of 12.96% per year, 6.71% with the first year excluded. In a national collaboration of academic centers in Ireland, the progression rate for NDBE was similar to recent population studies. Almost one in two who progressed was evident within 1 year. Crucially, LGD diagnosed and confirmed by specialist gastrointestinal pathologists represents truly high-risk disease, highlighting the importance of expertise in diagnosis and management, and providing indirect support for ablative therapies in this context.